Distinct clinical and pathological phenotypes in frontotemporal dementia associated with MAPT, PGRN and C9orf72 mutations. Issue 7 (27th November 2015) - Snowden, Julie S.; Adams, Jennifer; Harris, Jennifer; Thompson, Jennifer C.; Rollinson, Sara; Richardson, Anna; Jones, Matthew; Neary, David; Mann, David M.; Pickering-Brown, Stuart
Abstract: Our objective was to compare the clinical and pathological characteristics of frontotemporal dementia patients with MAPT, GRN and C9orf72 gene mutations. We carried out a cross-sectional comparative study of 74 gene-positive patients (15 MAPT, 17 GRN and 42 C9orf72 ). Thirty had post mortem pathological data permitting clinico-pathological correlation. MAPT patients were younger than other groups, and showed more frequent behavioural disinhibition, repetitive and stereotyped behaviours, semantic impairment and temporal predominance of atrophy. GRN patients were older at death and more likely to present with non-fluent aphasia. C9orf72 patients alone showed a co-occurrence of ALS. They showed more psychotic symptoms and irrational behaviour, yet were more often reported clinically as socially appropriate and warm. They showed less dietary change than other groups. C9orf72 patients with and without ALS differed only in frequency of psychosis. Greater clinical overlap was observed between GRN and C9orf72 compared to MAPT cases. MAPT cases had tau and GRN and C9orf72, with one exception, TDP-43 pathology. Non-fluent aphasia was linked to TDP subtype A in both GRN and C9orf72 cases and ALS with subtype B. In conclusion, the findings reinforce clinical heterogeneity in FTD and strengthen evidence that genotype influences clinical presentation. Clinical features may inform targeted genetic testing.